Professional integration as a boundary crossing: changes to identity and practice in immigrant engineers in Canada. Issue 3 (1st September 2016) - Friesen, Marcia
ABSTRACT: This work examines the qualifications recognition and career development experiences of internationally educated engineers (immigrants to Canada) through the interaction of boundary crossing and liberal fairness ideals embedded in the qualifications recognition process. The work explored how immigrant engineers experienced boundary crossing, evidence for learning at the boundary, and the dynamic tension between immigrant engineers' personal transitions within structural commitments to standardization and regulation. Data were collected from 18 voluntary participants who had immigrated to Canada and completed a qualifications recognition process to become registered as professional engineers in Canada and who were in active professional engineering practice. The data provided evidence of changes to immigrant engineers' personal identity and professional practice, where these changes were forms of learning that facilitated the boundary crossing from newcomer to legitimate participant in the Canadian engineering profession. However, the data did not provide evidence of learning as collaborative co-development of new processes for all actors – newcomers and long-time Canadians alike. Instead, the resilience of the Canadian profession to true integration in favour of an expectation of assimilation of newcomer practices into the Canadian mainstream was illuminated, due to the dominance of foundational commitments in the Canadian qualifications recognition processes to liberal fairness ideals as political mechanisms of risk reduction and access to the profession.